Content Centric Networking Based Secure Decentralized Data Management In V2G Environment - Miglani, Arzoo (My University, 2024)
Due to the increasing popularity of Electric vehicles (EVs) around the globe, vehicle-to-grid (V2G) has emerged as one of the most promising technologies of the modern era in modern smart grid ecosystems. In such systems, timely communications among different entities play a pivotal role in efficient decision-making. However, with an exponential increase in the number of EVs around the globe, it is challenging to assign a unique IP address to each EV for content delivery in V2G environment. Also, with an increase in the number of EVs, the traffic load on the network local area aggregator (LAG), (which aggregates the data between charging stations (CS), EVs and disseminates it among different participating entities) increases manyfold. Most of the existing solutions reported in the literature for the aforementioned problems are based upon traditional Internet Protocol (IP)-based architecture, which may have a performance degradation with an increase in the number of nodes in the network. Also, if the contents (for example, power, voltage profile measurements, and hourly electricity charges) need to be shared with multiple entities, then these contents are transmitted from a central source to each entity instantly, leading to wastage of resources. Also, the current Internet architecture lacks in-network caching, which is pre-requisite to take efficient decisions for fast content delivery. Hence, the model shift from existing TCP/IP-based architecture is required to solve the concerns raised in the current Internet architecture, for example, routing, address assignment, congestion, high data delay, scalability, and security. In comparison to traditional IP-based networks, content-centric networks (CCN) are widely used for efficient cache-based content sharing for the successful execution of efficient decisions in V2G network scenarios. In CCN, EVs can cache content to serve other nodes as per the requirements. As the same named data is cached at multiple locations in the network, so it can be retrieved from the nearest router, thereby reducing the network traffic and increased throughput. However, due to the selfish nature of EVs, they can only cache the content of their preferences. Also, in CCN, caching nodes separate the content from the content producer, depriving them of direct control over the content; thus, the content producer can’t fully trust the caching node to ensure secure data access. Moreover, to get benefits from content-based caching services, it is essential to match the service providers with service requesters optimally during high mobility vehicle scenarios. Most of the reported solutions for the aforementioned problems are centralized, so these may suffer from congestion problems and overhead generation and do not have fault tolerance capabilities. Moreover, the concern of trust for content delivery via caching still iv Arzoo Miglani, 901703016 poses threats to the network as content acquisition via CCN communication connects different network nodes, so nodes have concerns about untrusted users connected with them. Also, borderless caching at the network level may introduce multiple security and privacy challenges [1]. Consequently, some nodes may not be willing to participate as providers due to their concerns about privacy leakage or high energy consumption. This situation may create an imbalance in content supply and demand among network nodes. To mitigate the trust and privacy challenges, blockchain emerges as a promising technology that can be used to realize distributed access control. Blockchain ledger can record the hash value of contents to prevent data tampering attacks. As a solution to reduce the load on LAG, the first approach in this thesis proposes innetwork caching for fast content delivery in the V2G network. Particularly, we propose a contract theory based incentive scheme to attract vehicles to participate in content delivery to the recipients. The consortium blockchain network is used to store the reputation value and incentives-related transactions in the ledger of all nodes using blockchain. The performance of the proposed scheme illustrates that it outperforms the existing state-of- the-art schemes with respect to delay incurred, social welfare, throughput, and latency. In the second approach, we model the two-sided preferences of both parties (service providers and requesters) to maximize the cached content sharing CCN communications. Then, we formulated a decentralized matching problem with the joint transmit power of both the content providers and requesters. Finally, a distributed blind matching algorithm (BLMA) is proposed, which is executed by deploying a smart contract on the Ethereum network without involving an intermediate authority. The results obtained show that the proposed scheme is superior in comparison to the existing stateof-the-art solutions with respect to various performance evaluation metrics, including interest satisfaction rate, residual energy, throughput, and latency. Finally, to solve the issue of access control in CCN, we propose a ciphertext-policy attribute-based encryption (CP-ABE) scheme to secure one-to-many data sharing in which blockchain is used for maintaining verifiable access policy records to ensure non-repudiation. In the proposal, instead of one, multiple attribute centers are used for attribute management and secret key distribution; thereby, a single-point failure problem can be mitigated. Security and performance analysis demonstrates that the proposed scheme is superior in comparison to the existing benchmark schemes with respect to metrics such as encryption time, decryption time, key generation time, computational overhead, and storage overhead. To ensure secure content delivery and to achieve trust in the network, we propose the proof of authority (PoA) consensus algorithm among vehicles in the V2G network.
Keywords: V2G Networks; Content Centric Networking; Security and Privacy; NDN; Proof-of-Authority; Blockchain